Sequelae of Hemolytic Uremic Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The neuropsychological function of 91 children who had recovered from hemolytic uremic syndrome (HUS), without severe neurological dysfunction (stroke, hemiplegia, blindness, retardation), and case controls admitted for non-HUS illness, was determined in a multicenter study at six tertiary care hospitals reporting to the Canadian Pediatric Kidney Disease Research Center, Ottawa, Canada.